2019
DOI: 10.1093/mnrasl/slz109
|View full text |Cite
|
Sign up to set email alerts
|

The lowest detected stellar Fe abundance: the halo star SMSS J160540.18−144323.1

Abstract: We report the discovery of SMSS J160540.18−144323.1, a new ultra-metal poor halo star discovered with the SkyMapper telescope. We measure [Fe/H] = −6.2 ± 0.2 (1D LTE), the lowest ever detected abundance of iron in a star. The star is strongly carbon-enhanced, [C/Fe] = 3.9 ± 0.2, while other abundances are compatible with an α-enhanced solar-like pattern with [Ca/Fe] = 0.4 ± 0.2, [Mg/Fe] = 0.6 ± 0.2, [Ti/Fe] = 0.8 ± 0.2, and no significant s-or r-process enrichment, [Sr/Fe] < 0.2 and [Ba/Fe] < 1.0 (3σ limits). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 61 publications
3
68
0
Order By: Relevance
“…A sixth star, SMSS J160540.18-144323.1 first identified in this work, has also been shown to have [Fe/H] < -5; seeNordlander et al (2019). 2 see http://skymapper.anu.edu.au 3Beers & Christlieb (2005) use the terminology 'extremely', 'ultra' and 'hyper' metal-poor to designate stars with [Fe/H] < -3.0, -4.0 and -5.0, respectively.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…A sixth star, SMSS J160540.18-144323.1 first identified in this work, has also been shown to have [Fe/H] < -5; seeNordlander et al (2019). 2 see http://skymapper.anu.edu.au 3Beers & Christlieb (2005) use the terminology 'extremely', 'ultra' and 'hyper' metal-poor to designate stars with [Fe/H] < -3.0, -4.0 and -5.0, respectively.…”
supporting
confidence: 51%
“…For example, the most metal-poor star in this sample, SMSS J160540.18-1414323.1, which is the blue filled square symbol in the bottom panel of Fig. 9 and which has one of the highest W (G) values, is shown in Nordlander et al (2019) to be strongly carbon-enhanced ([C/Fe]1D,LT E = 3.9 ± 0.2). The other two stars with [Fe/H] f itter below -4 (the red filled triangle and the magenta open circle in Fig.…”
Section: Carbon Abundance Estimatesmentioning
confidence: 86%
See 2 more Smart Citations
“…Bond 1980;Beers et al 1985Beers et al , 1992McWilliam et al 1995;Cayrel et al 2004;Beers & Carollo 2008;Howes et al 2016) have revealed an interesting trend in the chemical composition of the lowest metallicity stars. Notably, there is an overabundance of carbon in some of the most iron-poor stars found in the halo of the Milky Way; indeed, every star with a measured iron abundance [Fe/H] ≤ −5.0 exhibits a strong carbon enhancement 1 (Christlieb et al 2004;Frebel et al 2005;Aoki et al 2006;Frebel et al 2015;Allende Prieto et al 2015;Nordlander et al 2019). Despite concentrated efforts, and increasingly sophisticated cosmological hydrodynamic simulations, we have yet to establish whether or not low mass (∼ 1 M ) metal-free stars can form.…”
Section: Introductionmentioning
confidence: 99%